THE PECULIARITIES OF THERMODYNAMIC FUNCTIONS AND Τ-PHASE - FILONENKO, Nataliia; BABACHENKO, Oleksandr; KONONENKO, Ganna; IVANOV, Nikita (My University, 2018)
Study was to determine the mechanism of formation, physical properties and thermodynamic functions cubicboroncarbideiron Fe 23 (CB) 6 [1-3].
Keywords: boride Fe 2 B; eutectics; cubic boron carbide Fe 23 (CB) 6; Gibbs energy; entropy; enthalpy; heat capacity